Korean missionaries in Southern Africa : a discussion and evaluation of Korean missionary activity in Southern Africa, 1980-2006 - Meiring, Piet (Pieter Gerhard Jacobus), 1941- (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2008.